6‐Methylenebicyclo[3.2.1]oct‐1‐en‐3‐one: A Twisted Olefin as Diels–Alder Dienophile for Expedited Syntheses of Four Kaurane Diterpenoids. Issue 44 (17th September 2019) - Wang, Junjie; Ma, Dawei
Abstract: 6‐Methylenebicyclo[3.2.1]oct‐1‐en‐3‐one, a twisted and highly reactive enone, was prepared for the first time by elimination of its bromide precursor. Its reactions as a dienophile with several dienes in Diels–Alder reactions proceeded smoothly to provide tricyclic and tetracyclic adducts, which allowed short syntheses (10–11 steps) of four kurane diterpenoids including 11β‐hydroxy‐16‐kaurene, 11α‐hydroxy‐16‐kaurene, liangshanin G, and gesneroidin B. Abstract : With a twist : 6‐Methylenebicyclo[3.2.1]oct‐1‐en‐3‐one, a twisted and highly reactive enone, was prepared for the first time by elimination of its bromide precursor. Its reactions as a dienophile with several dienes in Diels–Alder reactions proceeded smoothly to provide tricyclic and tetracyclic adducts, which allowed short syntheses (10–11 steps) of four kurane diterpenoids including 11β‐hydroxy‐16‐kaurene, 11α‐hydroxy‐16‐kaurene, liangshanin G, and gesneroidin B.